Peripheral Circumferential Chorioretinal Atrophy in a Patient with Alagille Syndrome - Shinji Makino; Hironobu Tampo CO (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2016)
The patient was a 15-year-old girl with an established diagnosis of Alagille syndrome (AS) since early life.  Her medical history was significant for systemic manifestations of AS including liver transplantation and pulmonary artery balloon dilation. She had an unusual triangular facies characterized by a broad  overhanging forehead, deep set, hyperteloric eyes and small pointed chin. Her bestcorrected visual acuity was 1.0 in both eyes. Slit-lamp examination was positive for posterior embryotoxon in both eyes.  Funduscopy revealed diffuse choroidal hypopigmentation with increased visibility of the choroidal vessels and symmetric, well-circumscribed macular discoloration (Figure 1). A circumferential chorioretinal atrophy was also detected in the peripheral retina (Figure 1). Fundus autofluorescence (FAF) imaging clearly defined hypofluorescent areas in the peripapillary regions that extended along the macula and had a sleep mask appearance (Figure 2). Peripheral circumferential chorioretinal atrophy was also clearly  etected (Figure 2).